Neurosurgical outcomes after intracerebral hemorrhage: results of the Factor seven for Acute hemorrhagic Stroke Trial (FAST) - Steiner, Thorsten; Vincent, Catherine; Morris, Stephen; Davis, Stephen; Vallejo-Torres, Laura; Christensen, Michael C. (Journal of stroke and cerebrovascular diseases, 2011)
The value of neurosurgical interventions after spontaneous intracerebral hemorrhage (SICH) is uncertain. We evaluated clinical outcomes in patients diagnosed with SICH within 3 hours of symptom onset who underwent hematoma evacuation or external ventricular drainage (EVD) of the hematoma in the Factor Seven for Acute Hemorrhagic Stroke Trial (FAST). FAST was a randomized, multicenter, double-blind, placebo-controlled trial conducted between May 2005 and February 2007 at 122 sites in 22 countries. Neurosurgical procedures (hematoma evacuation and external ventricular drainage) performed at any point after hospital admission were prospectively recorded. Clinical outcomes evaluated were post-SICH disability, as assessed by the modified Rankin Scale; neurologic impairment, as assessed by the National Institutes of Health Stroke Scale; and mortality at 90 days after SICH onset. The impact of neurosurgical procedures on clinical outcomes was evaluated using multivariate logistic regression analysis, controlling for relevant baseline characteristics. Fifty-five of 821 patients underwent neurosurgery. Patients who underwent hematoma evacuation or EVD were on average younger, had greater baseline neurologic impairment, and lower levels of consciousness compared with patients who did not undergo neurosurgery. After adjusting for these differences and other relevant baseline characteristics, we found that neurosurgery was generally associated with unfavorable outcomes at day 90. Among the patients who underwent hematoma evacuation, those with lobar ICH had less ICH expansion than those with deep gray matter ICH, and the smaller expansion was associated with lower mortality. ICH volume was substantially decreased in patients who underwent hematoma evacuation between 24 and 72 hours after hospital admission, and this was associated with better clinical outcome. In conclusion, a small number of patients who underwent neurosurgery in FAST exhibited no overall clinical benefit from neurosurgical intervention, although outcomes varied by type of surgery, time of surgery, and hematoma location. Our findings support the need for further research into the value of neurosurgery in patients with SICH.
Online verfügbar 10 Mai 2010
Gesehen am 21.10.2022